Evaluation of Students' Awareness of Charter of Patients\' Rights - Hadis Ashrafizadeh; Mahmood Maniati; Mohammad Adineh; Nasrin Elahi; Shahram Molavynejad; Safa Najafi (Iran University of Medical Sciences, 2019)
Background: As an essential principle, the collective life of human beings can constitute a human society only when human rights are respected. Demanding and respecting the rights of patients, as an inevitable part of human society, requires familiarity with patient-involved individuals. The present study aimed to determine the awareness level of Ahvaz Jundishapur University of Medical Sciences (AJUMS) students about the Charter of Patients' Rights (CPR).  Methods: This descriptive-analytical study was conducted on 200 senior university students who had been in contact with patients during their undergraduate program. They were invited from different faculties of the university. The data collection tool was a two-section questionnaire. The first section covered the demographic information, and the second included 29 questions about the 5 principles of the CPR. The obtained data were analyzed in SPSS by descriptive statistics, and analytical tests, including Independent Samples t-test, Analysis of Variance (ANOVA), and Spearman's correlation coefficient. Results: From the 200 study participants, 103 (51%) were female. The Mean±SD of students' awareness was 14.50±2.3. The highest and lowest mean scores belonged to the areas of access to services and confidentiality. There was no statistically significant difference between the awareness score of students from different faculties (P=0.359). Conclusion: This study results suggested that the awareness level of the medical students about the CPR was unsatisfactory. Instituting ethical codes among students and providing them knowledge of their professional lives is an essential part of the university's responsibilities.